A search for trachoma in Timor-Leste: no evidence to justify undertaking population-based prevalence surveys. (28th December 2018) - Correia, Marcelino; Brunner, David; Sharma, Manoj; Andrade, Valerio; Magno, Julia; Müller, Andreas; Pereira, Bernardete M.; Thumann, Gabriele; Verma, Nitin; Bangert, Mathieu; Kreis, Andréas J.; Solomon, Anthony W.
ABSTRACT: Purpose : We sought evidence to justify undertaking population-based trachoma surveys in Timor-Leste, believing that in the absence of such evidence, the country could be categorized as not needing interventions to eliminate trachoma. Methods : We undertook a systematic review of published literature on trachoma in Timor-Leste, with results updated to 28 April 2018. We also undertook a series of clinic- and field-based screening exercises, consisting of: (1) in October 2015, conjunctival examination of all children attending a school in Vila, Atauro Island; (2) from 1 November 2016 to 30 April 2017, examination for trichiasis, by specifically-trained frontline eye workers, of all individuals presenting to the ophthalmic clinics of six referral hospitals and five district eye clinics; and (3) house-to-house case searches in a total of 110 households, drawn from three communities that were reported by investigators from the 2016 Rapid Assessment of Avoidable Blindness (RAAB) to include residents with trachoma. Results : Three RAABs (2005, 2009–2010, 2016) and two relevant published papers were identified. The 2016 RAAB reported one female subject to have been diagnosed with trachomatous corneal opacity. Re-examination of that individual revealed that she had ankyloblepharon, without evidence of trichiasis or entropion. No children on Atauro Island, no clinic attendees, and no individuals examined in the targeted house-to-house searches had any sign of trachoma. Conclusion : Trachoma is very unlikely to be a public health problem in Timor-Leste. It would not be appropriate to incur the costs of conducting formal population-based trachoma prevalence surveys here.